Land consolidation, specialization, and household diets: Evidence from Rwanda - del Prete, Davide; Ghins, Léopold; Magrini, Emiliano; Pauw, Karl (International Food Policy Research Institute, 2018)
Despite rapid population growth, increasing land pressure and urbanization, farmers in Sub-Saharan Africa have not intensified their production in a sustainable manner and farming systems remain predominantly subsistence-oriented. Unsurprisingly, developing countries are directing large shares of their agricultural budgets to programs that actively promote crop intensification and the development of more commercially-oriented agricultural systems. Rwanda’s Crop Intensification Program (CIP), launched in 2007, is one such example. However, despite its apparent success in raising production of several priority crops, there are legitimate concerns about the food and nutrition security implications for households that are encouraged to consolidate their land, specialize in their production, and increasingly rely on markets for their food needs. Using recent household survey data and a propensity score matching difference-in-differences method, we find that participation in land consolidation activities had ambiguous consumption effects: it positively impacted on consumption of roots and tubers, but had a negative effect on meat, fish and fruits consumption and the potential availability of vitamin B12 in participants’ diets. This calls for a review of CIP implementation practices to enhance the program’s food and nutrition security outcomes, with improvements in market functioning and market access being potential starting points.